2019
DOI: 10.1039/c8nr08445a
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer dynamics in CsPbBr3 perovskite quantum dots–anthraquinone/fullerene (C60) hybrids

Abstract: An advantage of colloidal quantum dots, particularly perovskite quantum dots (PQDs), as photoactive components is that they easily form complexes with functional organic molecules, which results in hybrids with enriched photophysical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 63 publications
5
48
0
Order By: Relevance
“…[153,154] However, conjugated functional molecules may have proper HOMO-LUMO levels favorable for charge/energy transfer with perovskite NCs, forming a type of special nano-heterojunction. Some typical examples are shown in Figure 20, such as perovskite NCs modified by benzoquinone (BQ) and phenothiazine (PTZ), [155,156] functionalized cinnamic acid (R-CAH), [157] 1-naphthalene carboxylic acid (NCA), [158] 1-pyrenecarboxylic acid (PCA), [159] 1-ampinopyrene (AMP), [160] anthraquinone-2-carboxylic acid (AQ), [161,162] 5-tetracene carboxylic acid (TCA), [163] tetrathiophene ligands 4Tm and 4TCNm, [164] N3 dye, [165] and fullerene (C60). [162] The interlayer ligands of 2D layered perovskite also can be functionalized, e.g., chiral ligands would introduce chiral photonic properties.…”
Section: Subnanometric Heterojunctions: Organicmentioning
confidence: 99%
“…[153,154] However, conjugated functional molecules may have proper HOMO-LUMO levels favorable for charge/energy transfer with perovskite NCs, forming a type of special nano-heterojunction. Some typical examples are shown in Figure 20, such as perovskite NCs modified by benzoquinone (BQ) and phenothiazine (PTZ), [155,156] functionalized cinnamic acid (R-CAH), [157] 1-naphthalene carboxylic acid (NCA), [158] 1-pyrenecarboxylic acid (PCA), [159] 1-ampinopyrene (AMP), [160] anthraquinone-2-carboxylic acid (AQ), [161,162] 5-tetracene carboxylic acid (TCA), [163] tetrathiophene ligands 4Tm and 4TCNm, [164] N3 dye, [165] and fullerene (C60). [162] The interlayer ligands of 2D layered perovskite also can be functionalized, e.g., chiral ligands would introduce chiral photonic properties.…”
Section: Subnanometric Heterojunctions: Organicmentioning
confidence: 99%
“…12,3844 In doing so, hybrid QD-based donor–acceptor systems can be fabricated by band-gap engineering of the QD and of the QD–acceptor interface. 4557 Band-gap engineering of QDs allows to obtain optimal band alignment with the acceptor component in order to promote efficient photoinduced charge transfer. 39 Engineering of the donor–acceptor interface can further improve the efficiency of this process or it can allow rate tunability.…”
Section: Introductionmentioning
confidence: 99%
“…The extended functionalities of PQDs have been achieved by combining them with organic molecular electron donors and acceptors, preferably adsorbed on the surface of the PQDs to form ground-state complexes, and gaining photoinduced charge separation between PQDs and organic molecules. 3136 To the best of our knowledge the possibility of charge transfer from PQD multiexcitonic states has not been demonstrated yet.…”
mentioning
confidence: 99%
“…In our previous report, we showed that electron transfer from CsPbBr 3 PQD to AQ is thermodynamically favorable because the conduction band (CB) energy of PQD (−3.0 eV relative to the vacuum level) is higher than the lowest unoccupied molecular orbital (LUMO) of AQ (−3.5 eV relative to vacuum level) and observed electron transfer with a time constant of 30 ps. 36 Herein, we report on the study of MESs in CsPbBr 3 PQDs and multiple electron transfer from one multiexcited PQD to multiple electron acceptors, AQs in PQD–AQ hybrids, using ultrafast transient absorption (TA) spectroscopy. We show that as many as 14 excitons can be generated in one PQD at the highest excitation density used in this study and in the presence of AQ, 5 excitons are dissociated by electron transfer with the first electron-transfer reactions as fast as 1 ps.…”
mentioning
confidence: 99%
See 1 more Smart Citation